Volunteers' experiences of providing telephone-based breast-feeding peer support in the RUBY randomised controlled trial. Issue 16 (30th November 2020) - Grimes, HA; Shafiei, T; McLachlan, HL; Forster, DA
Abstract: Objective: The Ringing Up About Breastfeeding earlY (RUBY) randomised controlled trial (RCT) found that a telephone-based peer volunteer support intervention increased breast-feeding duration in a setting with high breast-feeding initiation. This sub-study of the RUBY RCT describes the motivation, preparation and experiences of volunteers who provided the peer support intervention. Design: An online survey was completed by 154 (67 %) volunteers after ceasing volunteering. Setting: Volunteers provided peer support to primiparous women ( n 574) who birthed at one of three public hospitals in Melbourne, Australia, between February 2013 and December 2015. Participants: Volunteers ( n 230) had themselves breastfed for at least 6 months and received 4 h of training for the role. Results: The median number of mothers supported was two (range 1–11), and two-thirds of respondents supported at least one mother for 6 months. Volunteers were motivated by a strong desire to support new mothers to establish and continue breast-feeding. Most (93 %) considered the training session adequate. The majority (60 %) reported following the call schedule 'most of the time', but many commented that 'it depends on the mother'. Overall, 84 % of volunteers were satisfied with the role and reported that the experience was enjoyable (85 %) and worthwhile (90 %). Volunteers agreed that telephone support for breast-feeding was valued by women (88 %) and that the programme would be effective in helping women to breastfeed (93 %). Conclusions: These findings are important for those developing similar peer support programmes in which recruiting volunteers and developing training requirements are an integral and recurrent part of volunteer management.